Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) terhadap Motivasi Belajar Pendidikan Agama Kristen Siswa Kelas VII SMP Negeri 1 Tarutung Tahun Ajaran 2023/2024 - Harianti Ropesta KM Limbong; Oktober Tua Aritonang; Goklas J. Manalu; Hasudungan Simatupang; Sudirman Lase (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The purpose of this study was to determine the positive and significant effect of the application of the Team Assisted Individualization type cooperative learning model on Christian Religious Education learning motivation of seventh grade students of SMP Negeri 1 Tarutung in the 2023/2024 Learning Year. The research method used is quantitative method with the type of pre-experimental design research with the form of “One Shot Case Study”. The population was all seventh grade students of SMP Negeri 1 Tarutung who were Protestant Christians totaling 175 people and a sample of 32 people was determined using Purposive Sample technique. Data were collected using a positive closed questionnaire of 20 items for variable X and an observation sheet of 22 items for variable Y. The results of data analysis are shown through: 1) Analysis requirements test: a) positive relationship test obtained rxy = 0.560 > rtable (=0.05, n=32) = 0.349. b) significant relationship test obtained tcount = 3.704 > ttable (=0.05, dk=n-2=30) = 2.042. 2) Effect test: a) Regression equation test, obtained regression equation Y ̂ = “33.23”+0.58X. b) Regression determination coefficient test (r2) = 31.4%. 3) Hypothesis testing using the F test obtained Fhitung> Ftabel = (=0.05, dk numerator k = 21, dk denominator = n-2 = 32-2 = 30), namely 13.70> 1.62. Thus Ha is accepted and H0 is rejected. So, the study concluded that there is a positive and significant effect of the Application of Team Assisted Individualization Type Cooperative Learning Model on Christian Religious Education Learning Motivation of Class VII Students of SMP Negeri 1 Tarutung Learning Year 2023/2024.